Commentary: Branded Content and Media-Marketing Convergence - Hardy, Jonathan (The Political Economy of Communication, 2017)
Your Facebook feed says "Recommended for you" and "Sponsored". Your online magazine says "Paid Content", another in Buzzfeed (2014) says "Promoted Content" and lists "12 Backpacking Hacks That Are Vital For Business Trips" in an article paid for by Holiday Inn Express. Buzzfeed may also list KFC as "Brand Publisher" for an article, "11 Things All Busy Families Should Make Time For", including KFC's Popcorn Nuggets (Buzzfeed, 2015). You read a powerful series of articles on hunger in America, but it is labelled "paid programme", produced by the Wall Street Journal's Custom Studios in collaboration with Mini, and includes such branded wisdom as "Mini owners are all different. There's no one person that Mini drivers look like. It's the same with food insecurity. It's all walks of life". From television product placement to mobile news feeds, brands are burrowing into media content. Exploring that merging of media and marketing was a key impetus behind the Branded Content Research Network, launched in late 2016. It aims to facilitate collaboration between academics, industry professionals and civil society to explore branded content practices and their media policy implications. Here are my reflections on some of the research tasks and policy issues arising from this collective endeavour.